2022
DOI: 10.3389/fgene.2022.787141
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Therapeutic Perspectives of CXCR Members in the Glioma Microenvironment

Abstract: Background: CXCR (CXC Chemokine Receptor) is a complex of the immune-associated protein involved in tumor activation, invasion, migration, and angiogenesis through various chemical signals in the tumor microenvironment (TME). However, significant prognostic characteristics of CXCR members and their impact on the occurrence and progression of glioma have not yet been fully elucidated.Methods: In this research, we used Oncomine, TCGA, GTEx, and CGGA databases to analyze the transcription and survival data of gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…We found that CXCR4 is closely related to the prognosis of patients with GBM and preliminarily verified that CXCR4 is an important index to judge the prognosis of patients with GBM. Our previous study found that the prognosis of GBM with high expression of CXCR4 was worse, which was consistent with that reported in the literature [ 26 ]. Secondly, based on t-ROC and DCA to build a high-precision GBM prognosis prediction model to verify its application value in GBM patients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We found that CXCR4 is closely related to the prognosis of patients with GBM and preliminarily verified that CXCR4 is an important index to judge the prognosis of patients with GBM. Our previous study found that the prognosis of GBM with high expression of CXCR4 was worse, which was consistent with that reported in the literature [ 26 ]. Secondly, based on t-ROC and DCA to build a high-precision GBM prognosis prediction model to verify its application value in GBM patients.…”
Section: Discussionsupporting
confidence: 92%
“…A growing number of studies have shown that the CXCR members are frequently involved in tumorigenesis and development and play an essential role in antitumor immunity [ 25 , 26 ]. However, the clinical value and application of the CXCR members in primary GBM has not been thoroughly clarified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, neutrophil can stimulate dormant cancer cells through release of MMP9 which can produce epitopes that bind to tumor integrins and trigger the proliferation of cancer cells [26,27]. It has been reported that CXCR1 mRNA expression is significantly higher in patients with glioma than in normal individuals [64]. The tumor-promoting activity of neutrophils was related to growth factors and chemotactic factors [53,65,66], and CXCR was involved in promoting neutrophil maturation, survival, and recruitment [18,[67][68][69].…”
Section: Discussionmentioning
confidence: 99%